Identification of Scientific Literacy of Elementary School Students in Central Lampung District - Rakhmawati, Ismi; Kadaritna, Nina; Rosidin, Undang; Sari, Novinta Nurul (Jurnal Pendidikan Progresif, 2020)
Identification of Scientific Literacy of Elementary School Students in Central Lampung District. Objective: Identify scientific literacy skills of elementary school students that can be actualized in the form of local government policies. Method: This descriptive study involved 36 schools with a total of 380 Elementary School students in Lampung Tengah District obtained using purposive sampling technique. Students examined with scientific literacy questions adapted from PISA (Programs for International Student Assessment) question items and scientific literacy data are analyzed descriptively. Findings: The research data shows that students who understand concepts of science are only 16.07%, misconcept are 8.6%, mistaken are 37.5%, and not understand are 37.8%. Elementary students who understand the concepts of science are still fewin all knowledge categories which are factual category 16.75%, conceptual 16.08%, and procedural 13.5%. Conclusion: Elementary students’ scientific literacy in Central Lampung is still in the low category.Keywords: scientific literacy, elementary school students, descriptive study.